MODEL TEACHERPRENEUR PADA PEMBELAJARAN VOKASI MENGHADAPI ERA DISRUPSI DAN REVOLUSI INDUSTRI 4.0 - Wisnu Rachmad Prihadi (Universitas Negeri Yogyakarta, 2019)
ABSTRACT This study aims: (1) to examine the grand design of the teacherpreneur model in vocational education on the development of the industrial revolution and disruption. This research uses descriptive method based on literature review. The results of the study show that: The teacherpreneur model for preparing learning in the industrial revolution 4.0 era that was developed was composed of four pillars namely competency, creativity, effectiveness, collaboration. needed the addition of a pillar of collaboration as a time of growing rapidly. In this model it is necessary to retest both internally related to the effectiveness of the model before it is applied. although it can be seen at the beginning for the initial model that has a pretty good score, i.e. (a) the model components are complete (92.83%); (b) the structure of the model components is clear (91.65%); (c) the relationship between the components of the model is clear (95.83%); (d) the model readability has been good (95.83%); (e) the model is feasible (95.83%); and (f) effective models if implemented (87.5%). Keywords: development, pilars, teacherpreneur ABSTRAK Kajian ini bertujuan: (1) mengkaji grand design model teacherpreneur pada pendidikan kejuruan terhadap perkembangan revolusi industri dan disrupsi. Penelitian ini menggunakan metode deskriptif berdasarkan kajian literatur. Hasil kajian menunjukkan bahwa: Model teacherpreneur untuk menyiapkan pembelajran di era revolusi industri 4.0 yang dikembangkan tersusun atas empat pilar yaitu kompetensi, kreatifitas, efektivitas, kolaborasi. diperlukan penambahan pilar kolaborasi sebagai tutntutan zaman yang begitu berkembang pesat. Pada model ini perlunya dilakukan pengujian ulang baik secara internal terkait keefektifan model sebelum diterapkan. walapun dapat dilihat diawal untuk model awal memiliki skor yang cukup baik yaitu (a) komponen model telah lengkap (92,83%); (b) struktur komponen model telah jelas (91,65%); (c) hubungan antar komponen model telah jelas (95,83%); (d) keterbacaan model telah baik (95,83%); (e) model telah layak (95,83%); dan (f) model efektif jika diimplementasikan (87,5%). Kata Kunci: pengembangan, pilar, teacherpreneur